Visual soccer match analysis using spatiotemporal positions of players. (November 2017) - Machado, Vinicius; Leite, Roger; Moura, Felipe; Cunha, Sergio; Sadlo, Filip; Comba, João L.D.
Highlights: A system for the visual analysis of soccer matches based on the spatiotemporal position of players. A matrix-oriented design that allows displaying the position of players and tactical schemes throughout the match. A visual summarization using pathline glyphs of the player trajectories that started from a given region in the field. Evaluation of the visual design by soccer experts. Graphical abstract: Abstract: Soccer is a fascinating sport that captures the attention of millions of people in the world. Professional soccer teams, as well as the broadcasting media, have a deep interest in the analysis of soccer matches. Statistical summaries are the most widely used approach to describe a soccer match. However, they often fail to capture the evolution and changes of strategies that happen during a game. In this work, we present visual designs to help understanding a soccer match from the spatiotemporal position of players. We receive as input the coordinates of each player throughout the match, as well as the associated events. We present a pixel-oriented layout that summarizes the changes of player positions and tactical schemes during the match. Also, we revisit a technique used for flow analysis to help us identify where does a player move from a given region in the field. We developed our approach in conjunction with colleagues from physical education with experience in soccer analysis, as well as experts on soccer data extraction. We demonstrate the utility of our approach in several match situations, and provide the feedback given by the experts.